The Quality of Pedestrian Based on Pedestrian Environment Quality Index (PEQI) Standards in the Cultural Heritage Area of Tunjungan Street Surabaya - Iffiyah, Khoudiy; Santoso, Eko Budi; Setiawan, Rulli Pratiwi (BERKALA SAINSTEK, 2022)
Tunjungan Street is one of the historical tourist destinations and one of the Cultural Conservation Areas in Surabaya. The use of pedestrian in Tunjungan Street is classified as high because it is a downtown area with various activities and its use as a pathway to access Cultural Conservation buildings. Many visitors use the pedestrian as an area to enjoy the Cultural Conservation building while walking along Jalan Tunjungan or as a photo point with the Cultural Heritage building in the background. This study aims to analyze the quality of pedestrian to determine the feasibility of infrastructure and pedestrians so that they can be an indicator of the completeness of pedestrian facilities in the Tunjungan Street Cultural Heritage Area. In this study, the problems that exist in the existing condition of the pedestrian path are investigated and studied regarding the quality of the pedestrian. The method used in this study was a quantitative method by assessing the quality of the pedestrian and scoring based on the Pedestrian Environmental Quality Index (PEQI) standard on both pedestrian sections of Jalan Tunjungan. This study indicates that the pedestrian in the Cultural Heritage Area of Jalan Tunjungan Surabaya meets the basic quality according to the calculation of the PEQI index with a total score of 60.77. This means that the pedestrian in the Cultural Heritage Area of Jalan Tunjungan Surabaya is suitable for use as a pedestrian that pays attention to the safety of road users for all. However, improving the quality of the pedestrian path to a reasonable rate will be better so that visitors can enjoy the pedestrian path facilities more appropriately and become the main attraction for visitors and become the pride of the people around the Cultural Conservation Area.